Race, law, and health: Examination of 'Stand Your Ground' and defendant convictions in Florida. (October 2015) - Ackermann, Nicole; Goodman, Melody S.; Gilbert, Keon; Arroyo-Johnson, Cassandra; Pagano, Marcello
Abstract: Previous analyses of Stand Your Ground (SYG) cases have been primarily descriptive. We examine the relationship between race of the victim and conviction of the defendant in SYG cases in Florida from 2005 to 2013. Using a regression analytic approach, we allow for simultaneous examination of multiple factors to better understand existing interrelationships. Data was obtained from the Tampa Bay Times SYG database (237 cases) which was supplemented with available online court documents and/or news reports. After excluding cases which were, still pending as of January 2015; had multiple outcomes (because of multiple suspects); and missing information on race of victim and weapon of victim, our final analytic sample has 204 cases. We chose whether the case resulted in a conviction as the outcome. We develop logistic regression models using significant bivariate predictors as candidates. These include race of the victim (White, non-White), whether the defendant could have retreated from the situation, whether the defendant pursued the victim, if the victim was unarmed, and who was the initiator of the confrontation. We find race of the victim to be a significant predictor of case outcome in this data set. After controlling for other variables, the defendant is two times (OR = 2.1, 95% CI [1.07, 4.10]) more likely to be convicted in a case that involves White victims compared to those involving non-White victims. Our results depict a disturbing message: SYG legislation in Florida has a quantifiable racial bias that reveals a leniency in convictions if the victim is non-White, which provides evidence towards unequal treatment under the law. Rather than attempting to hide the outcomes of these laws, as was done in Florida, other states with SYG laws should carry out similar analyses to see if their manifestations are the same as those in Florida, and all should remediate any injustices found. Highlights: We examine racial bias related to the "Stand Your Ground" statute in Florida. We find race of the victim to be a predictor of conviction of the defendant. Conviction is more likely in cases of White victims versus non-White victims. Stand Your Ground legislation in Florida has a quantifiable racial bias.